POTRET TRANSFORMASI MASYARAKAT PEGUNUNGAN JAWA STUDI KASUS: SIPETUNG KABUPATEN PEKALONGAN JAWA TENGAH - Fajri Rahman (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2015)
This article will try to explain how agricultural transformation that occurred in Dukuh Sipetung, Tlogopakis, District Petungkriyono, Pekalongan Central Java. Agricultural transformation is basically the process of change in various aspects of agriculture. In this paper, there are three aspects that cause the transformation: population growth, market  dynamics, and development agendas faced by society Sipetung. In addition, also described how people in Sipetung respond and interpretation the transformations occurring proficiency level